A computed tomographic, mixed dentition, space analysis comparison - Queijo Luís; do Vale Francisco; Corte-Real Ana; Alves Sónia (Sciendo, 2016)
A considered space analysis aims to predict the combined mesiodistal widths of unerupted permanent canine and premolars. A miscalculation can lead to the application of inadequate and irreversible treatments.